EFEKTIVITAS PELATIHAN REGULASI METAKOGNISI UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN PROBLEM MATEMATIKA - Henu Cahyani, Berliana (Universitas Ahmad Dahlan, 2010)
The aim of this research was to identify the effectiveness of metacognition regulation training to increase the ability of math problem solving. The research subjects were 20 high school students at XI grade in science major. They were randomly divided into two groups, experiment group and control group. Mann Whitney-U Test was used to analyze change in ability of math problem solving through gained score. The result shows there is no difference between experiment group and control group after training (Z=-0.189, p=0.850, p>0.05). The research result shows that metacognition regulation training is not effective to increase the ability of math problem solving.